Parametric Study of Continous Composite Steel-Concrete Beam with External Prestressing - Amer M. Ibrahim; Wissam D. Salman (Engineering and Technology Journal, 2015)
In the present study, three-dimensional nonlinear finite element analyses were conducted to investigate the effect of several important parameters on the behavior of the external prestressed continuous composite steel-concrete beam. These parameters included the effects of concrete compressive strength, ratio of effective prestressing to ultimate stress (fpe/fpu), external prestressing technique, ratio of thickness to width of concrete slab (T/B), transfer load point to mid span section, type of loading, full and partial interaction, tendon profile, and number of stiffeners. It had been found that, at increasing the concrete compressive strength from (20 to 60MPa) and the ratio of prestress to ultimate stress from (0.264 to 0.79), the ultimate load was increased by about (19.64%) and (9.05), respectively. The ultimate load of a continuous composite beam with external prestressing was increased by about (26.63%) than the same continuous beam without prestressing. The increase in the ultimate load of the continuous beam subjected to three point loads on each span was (25.93%) larger than that of the continuous beam with a single load on each span. It was noted that the ultimate capacity was increased by (7.32%) when draped tendon profile was used. Also it was noted that the ultimate load of beam with full interaction is (3.25%) greater than the same beam with partial interaction. Increasing the thickness to width of concrete slab ratio, from (0.1 to 0.25) with constant area of concrete, led to an increase in the ultimate load by about (6.60%). It was noted that the ultimate capacity increased by about (8.25%) when number of stiffeners were increased from three to seven.